Private Developers’ Viewpoint on Residential Development in the Peri-Urban of Greater Bandung Area - Anita Vitriana (Department of Urban and Regional Planning, Diponegoro University, 2020)
Over the past 30 years, Bandung city has experienced with rapid urban land expansion. Together with nearby regencies, it has formed a conurbation urban area namely the Metropolitan Bandung Area. The growth of Greater Bandung is performed by the increasingly widespread of urban settlements in the outer surrounding region of Bandung city. Most of new residential areas are developed in the suburbs area and carried in formal land development initiated by private developers. The study aims to examine how spatial irregularities can be produced through the formal land development framework. This research was conducted with a qualitative approach. Primary data was obtained using purposive sampling interview. Interviewee came from 14 medium-large residential private developers. The data was written down in the interview transcript to be analysed with qualitative content analysis method. The result shows developers strive to develop profit-oriented land. They look for pragmatic solutions based on economic principles as long as no permit violation. Developers would not think deeply for the broader impact of the project since it is not their obligation. Developers will automatically support sustainable peri-urban development if the government provides clear, applicable and consistent rules and guidelines.